DNA vaccine for hepatitis B: evidence for immunogenicity in chimpanzees and comparison with other vaccines. - Davis, H L (1996)
Vaccination of two chimpanzees against hepatitis B virus (HBV) by intramuscular injection of plasmid DNA encoding the major and middle HBV envelope proteins induced group-, subtype- and preS2-specific antibodies. These were initially of IgM isotype, and then they were of IgG (predominantly IgGl) isotype. The chimpanzee injected with 2 mg of DNA attained >100 milli-international units/ml of anti-HBs antibody after one injection and 14,000 milli-international units/ml after four injections. A smaller dose (400 microg) induced lower and transient titers, but a strong anamnestic response occurred 1 year later. Comparison with responses in 23 chimpanzees receiving various antigen-based HBV vaccines suggests that the DNA approach is promising for prophylactic immunization against HBV.